Extraction and Characterization of Starch from Cassava Peels. (22nd March 2022) - Fronza, Pãmella; Costa, Ana Letícia Rodrigues; Franca, Adriana Silva; de Oliveira, Leandro Soares
Abstract: Cassava peels are waste generated worldwide in large amounts by the cassava processing industry. Although some studies have highlighted their application for animal feed, a more profitable use for these residues has not yet been implemented. Thus, the aim of this study is to extract starch from the peels of cassava and to characterize its physical, chemical, rheological, structural, thermal, and morphological properties. The content (23.2%) and the properties of the starch extracted from cassava residues are within the ranges of those extracted from the flesh, and of those from other sources such as corn and sorghum. Centesimal composition data show low contents of proteins, ash, and lipids. The extracted starch presents an amylopectin‐to‐amylose ratio of 5:1, which facilitates gelatinization and contributes to high solubility and swelling power, highly desirable properties for food applications. The high thermal stability of the extracted starch suggests strong intermolecular and intramolecular interactions of the starch molecules, a characteristic that favors its application in processes where elevated temperatures are applied. Abstract : Cassava periderm and cortex are wastes generated worldwide in large amounts. In this study, it is found that the properties of the starch extracted from cassava residues are similar to starch from other sources, therefore this starch can be used in various segments in the food industry, thus adding value to these residues and reducing the environmental impact from its disposal.